IMPLEMENTASI PROGRAM JARING PENGAMAN SOSIAL PADA MASA PANDEMI COVID-19 DI PEKANBARU - Hidayati Nasrah; Irdayanti Irdayanti; Yessi Nesneri; Fitri Hidayati (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
AbstractThis research describes how the social safety net program, especially during the pandemic Corona virus in Pekanbaru, which has been going on for quite long. The method used in this research is a qualitative with descriptive analysis. Data collection techniques used were interviews, observation and documents related to the implementation of the assistance program. Furthermore, the data is processed through triangulation techniques. To analyze this implementation policy, the implementation theory of Van Meter and Van Horn is used by looking at 6 indicators of success they are goals, resources, implementing agents, implementing agent attitudes, agent communication and external environment. The results show that the implementation of the assistance program during the Covid-19 pandemic has been running from April 2020 to Desember 20202 when the program objectives were set. However, there is no similarity in implementation based on procedures due to factors, including the expansion of several sub-districts and the absence of a standard measure of success in implementing this assistance program in Pekanbaru.